THE USE OF THINK PAIR SHARE WITH PICTURE TO IMPROVE STUDENTS' WRITING SKILL - Ni Ketut Karin Asih; Ida Bagus Nyoman Mantra; Anak Agung Istri Yudhi Pramawati (Academic Journal on English Studies (AJOES), 2023)
The study aims to find out whether or not Think Pair Share can improve the writing skills of 10th graders of SMA Negeri 1 Manggis in school year 2022/2023. The subject of this study were the tenth grade students of the SMA Negeri 1 Manggis. Class X H students chose the subject, which consists of 31 students. The research used the classroom action research type. The research was carried out by Think Pair Share with image and divided into several cycles, each consisting of two cycles. In this study, two kinds of data were obtained from the result of the pre-test, the post-test and the questionnaire. The mean score result showed an improvement over the pre-test from 48.77 to 70.09 in post-test I and 83.09 in post-test II. The investigators administered the questionnaire at the end of Cycle II. The percentage showed that the opinions of the questionnaire 66.83% strongly agree. These results supported the main findings of the study. In addition, it was found that subjects gave good responses to the implementation of Think Pair Share with Picture to improve writing skills.